Crime and Punishment: jihadist Financing and Criminal Accountability in Finland - Tuomaala-Järvinen, Lotta (Perspectives on terrorism, 2021)
This article provides the first-ever empirical overview of patterns of jihadist financing in Finland. As jihadism has evolved in the country, particularly during the 2010s, financing-related activities have become increasingly present, also developing in quality and variance. While there are no upheld convictions on terrorist financing in Finland to date, the authors have identified at least three distinct types of jihadist financing present in the country. First, assets have been raised and moved to armed jihadist groups operating in conflict zones abroad. Second, foreign fighters traveling to Syria and Iraq, predominantly to join IS, have self-financed their travel and equipment purchases, partly through illicit means, and, in at least one case, also moved assets for the benefit of the group they joined. Lastly, there have been assets raised in Finland and moved to individuals engaging in jihadist activities abroad. However, Finland faces notable challenges in investigating and prosecuting these offenses, hampering its efforts to promote criminal accountability for terrorist offenses.